Aktivitas hepatoprotektor ektrak etanol daun durian ((Durio zibethinus Murr.) pada mencit yang diinduksi parasetamol - Puspa Dwi Pratiwi; Nazrah Tiara; Intan lestari (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Durian (Durio zibethinus Murr.) have been studied and reported has antioxidant activity and its potential as hepatoprotector. This study was determined the hepatoprotector activity and effective dose of ethanol extract of durian (Durio zibethinus Murr.) leave on mice. This experiment was experimental study using completely randomized design (CDR) with a post-test only control group design used 35 mice were divided into 5 treatment groups: negative control (NaCMC), positive control (acetaminophen 5.07 mg/20g bodyweight), treatment 1 (125 mg extract/kg bodyweight), treatment 2 (250 mg extract/kg bodyweight), and treatment 3 (500 mg extract/kg bodyweight). Secondary metabolites of extract, SGPT and SGOT of mice’s blood, and histopathology of mice’s liver was observed. This study showed that extract contained alkaloid, flavonoid, phenolic, and saponis. From SGPT and SGOT value, the results showed that the higher the extract was given, the level of SGPT and SGOT value decreased. Our study revealed that ethanol extract of durian leaves has activity as hepatoprotector and the effective dose was 500 mg/kg bodyweight.